Profile of Critical Thinking Results Analyzed from Facione Indicators and Gender of Learners - Rima Arini; Yuni Sri Rahayu; Erman Erman (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2023)
Objective: This research aims to describe the results of students' critical thinking in three different junior high schools. This research was conducted using a quantitative descriptive method in which the data obtained were the results of the critical thinking of male and female Grade VIII students from three different junior high schools in Pamekasan, namely in the Tlanakan, Galis, and Larangan areas using thinking indicators. Fionce's Critical Thinking on Narcotics, Psychotropics, and Other Addictive Substances, Fionce's critical thinking indicators are as follows Interpretation, Analysis, Evaluation, Conclusion, Explanation, and Self-Regulation Methods: The method used in this study was to have students work on five critical thinking essay questions by taking random samples. Results: From the three junior high schools, a sample of 50 students was obtained, namely 25 male and 25 female students. After the students worked on the questions, the average male student scored 62.56, and the female student scored 65.28. Novelty: From the results obtained, it was found that the average score of female students was higher than that of male students from three different schools based on an analysis of the Fionce indicators where female students tended to give more detailed and thorough answers than male students. The second reason female students have higher critical thinking skills than male students is that the answers given by male students tend to be different from the topics in the questions given by the researcher.